Response Of Almond Seedlings Growth To Foliar Spraying Of Amino Plasma, Zinc, Boron And Their Interactions - Nabi, Hasan Saleem; Barwary, Naji Isam Hussein; Tayib, Azad Ahmed; Sulaiman, Hussein Moho (Sulaimani Journal for Pure and Applied Sciences, 2018)
This investigation was carried out during growing season (2016) on Almond seedling belongs to Agriculture College, University of Duhok, to investigate the effect of amino plasma, Zinc, boron and their concentrations (0, 200, and 250 ml.L-1), (0, 100, and 200 mg.L-1), and (0, 300, and 400 mg.L-1), respectively, on vegetative growth of almond seedlings. Accordingly the obtained results reveal that the amino plasma lead to enhance most studied parameters except of (No. of branch.plant-1 and leaf fresh weight). Zinc and boron at (200 and 400 mg.L-1), respectively cause significant increase in all studied parameters. The high level of Amino plasma, Zinc and boron in interactions among them lead to enhance all studied parameters. It concluded their spray of Amino plasma, Zinc and Boron was affectingly improved growth of Almonds.
Keywords: Almond seedling; amino plasma; Zinc; Boron